Mondialité or The Archipelagos of Édouard Glissant - Obrist, Hans Ulrich; Raza, Asad (Paris : SKIRA, 2017)
Adami, Valerio ; Adonis ; Adnan, Etel ; Al-Maria, Sophia ; Attia, Kader ; Barcelo, Miquel ; Boetti, Alighiero ; Boyd, Dan ; Dekyndt, Edith ; Diawara, Manthia ; Fattal, Simone ; Gallego, Geneviève ; Glissant, Sylvie et al.
This catalogue was designed for the Mondialité, or the archipelagos of Edouard Glissant exhibition. Mondialité features visual artworks and environments, documentary film and songs, dramaturgical structures and archival material. Building on the experimental exhibitions that Obrist curated and Raza co-created dramaturgies for, Solaris Chronicles and A stroll through a fun palace, the exhibition unfolds in time as well as expand across space. Mondialité aims to bring visitors into contact with Glissant’s thought and the urgency of returning to its terrain, a relational form of perceiving and thinking. For the book Mondialité; or the archipelagos of Edouard Glissant, artists and thinkers contribute texts, excerpts and images to a commonplace book that explores key Glissantian concepts such as pensée du tremblement, créolisation, and opacité.(from The Boghossian Foundation)
Mondialité, The Boghossian Foundation, Brussels, 19 april to 27 august 2017
boek
Keywords: Glissant, Édouard